Prevalence of vitamin D and B12 deficiency in pregnant women in Jammu, India - Kaur, Sapneet; Kaur, Harleen (International Journal of Research in Medical Sciences, 2020)
Background: Micronutrient deficiency is pandemic proportions among pregnant women in India, but there is scarcity of searchable data on coexistence vitamin D status and Vitamin B 12 in pregnant women in Jammu and Kashmir, hence we have assessed the vitamin D as well as Vitamin B12 status in pregnant women attending outpatient department in a tertiary care hospital Jammu. Methods: The study was conducted in the department of Biochemistry Government Medical College Jammu during June 2019 to February, 2020 and after obtaining informed consent, a total of 150 pregnant women, attending SMGS Hospital Jammu were screened for their vitamin D (25 OH-D) and vitamin B12 status by using Abbott architect chemiluminescent micro particle immunoassay. Results: A total of 150 pregnant women were screened in the study , 129 (86%) were found to be having insufficient vitamin D levels in their blood (<30 ngm/dl) and 105 ( 70%) women showed severe deficiency with vitamin D levels below 20 ngm/dl.108 (72%) pregnant women had vitamin B12 deficiency with levels below 200 pgm/ml. Conclusions: The study revealed a high prevalence of coexistence of Vitamin D and Vitamin B12 deficiency in pregnant women, despite of abundant sunshine throughout the year and also with the consideration that people of this region are well off economically and can afford good nutrition.